IMMUNOLOGICAL STUDY OF SOME BIOMARKER IN CELIAC DISEASE IN BASRAH PROVINCE - Othafa, Duaa Faiz; Mahdi, Dawood S.; Al-Saimary, Ihsan Edan (PT. Antis International Publisher, 2025)
Objective: This study investigates the diagnostic accuracy of IgG anti-deamidated gliadin peptide (DGP), IgA and IgG anti-tissue transglutaminase (tTG), IgG anti-gliadin (AGA), and IgG anti-endomysial antibodies (EMA) in diagnosing celiac disease (CD), particularly in patients with IgA deficiency. Methods: A case-control study was conducted with 118 participants, including 68 newly diagnosed CD patients and 50 healthy controls. Serum samples were collected and analyzed using the Sandwich-ELISA technique. Statistical analysis included chi-square tests, ANOVA, logistic regression, and Spearman correlation, using SPSS v26. Results: Antibody concentrations were significantly elevated in CD patients compared to controls (p = 0.0001). Median levels of anti-gliadin IgG, EMA IgG, DGP IgG, tTG IgA, and tTG IgG in patients were 40.8 ng/ml, 345.5 pg/ml, 11.5 nml/l, 2.85 ng/ml, and 95.5 ng/ml, respectively. Significant inverse correlations were observed between gliadin-IgG and EMA (-30.2%, p = 0.012), tTG IgA (-23.8%, p = 0.0001), and tTG IgG (-39.7%, p = 0.001). EMA demonstrated direct correlations with DPG (49%, p = 0.0001), tTG IgA (36.4%, p = 0.002), and tTG IgG (34.1%, p = 0.004). Novelty: This study highlights the diagnostic utility of IgG anti-DGP as a reliable marker in IgA-deficient populations and underscores the correlations among antibody markers, providing insights into their synergistic roles in CD diagnosis.